2014
DOI: 10.1530/eje-13-1008
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoma in childhood: clinical, radiological, molecular and histological aspects of nine patients

Abstract: Background: Insulinomas are a rare cause of hyperinsulinaemic hypoglycaemia (HH) in children. The clinical features, investigations, management and histology of these rare pancreatic tumours in children have not been described in a large cohort of patients. Methods: We conducted a retrospective review of cases diagnosed between 2000 and 2012, presenting to two referral centres in the United Kingdom. Clinical, biochemical, imaging (magnetic resonance imaging (MRI) and 6-L-18 F-fluorodihydroxyphenylalanine ( 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 24 publications
2
36
0
1
Order By: Relevance
“…The most accepted modality of treatment for patient with insulinoma is surgical resection. In the absence of preoperative localization and failed intraoperative detection of an insulinoma, blind pancreatic resection is not recommended [4]. Preoperative tumor localization may require many imaging modalities for avoiding unsuccessful blind pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The most accepted modality of treatment for patient with insulinoma is surgical resection. In the absence of preoperative localization and failed intraoperative detection of an insulinoma, blind pancreatic resection is not recommended [4]. Preoperative tumor localization may require many imaging modalities for avoiding unsuccessful blind pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…W.H. Peranteau et al reported 50% (3/6), while R. Padidela et al reported 88% (7/8) correct localisation of the lesion with MRI (2). Octreotide scans have poor detection of insulinoma as they usually do not express enough somatostatin receptors (13).…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide scans have poor detection of insulinoma as they usually do not express enough somatostatin receptors (13). 18F-DOPA is taken up by neuroendocrine cells and used to differentiate between focal and diffuse lesions in congenital hyperinsulinism; 18F-DOPA PET scan is inconsistent in localising insulinoma in children: 100% (3/3) in one series and 50% (2/4) in another (2, 3). Glucagon-like peptide 1 (GLP1) receptor imaging is a new and non-invasive modality, which has shown 100% successful localisation in a small study of six cases (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations